Below-ground biomass and productivity of a grazed site and a neighbouring ungrazed exclosure in a grassland in central Argentina - Pucheta, Eduardo Raúl (2004)
We estimated the below-ground net plant productivity (BNPP) of different biomass components in an intensively and continuously 45-ha grazed site and in a neighbouring exclosure ungrazed for 16 years for a natural mountain grassland in central Argentina. We measured approximately twice as much dead below-ground biomass in the grazed site as in the ungrazed site, with a strong concentration of total below-ground biomass towards the upper 10 cm of the soil layer in both sites. The main contribution to total live biomass was accounted for by very fine (<0.5 mm) and fine roots (0.5-1.0 mm) both at the grazed (79%) and at the ungrazed (81%) sites. We measured more dead biomass for almost all root components, more live biomass of rhizomes, tap roots and bulbs, and less live biomass of thicker roots (>1 mm) in the grazed site. The seasonal variation of total live below-ground biomass mainly reflected climate, with the growing season being limited to the warmer and wetter portion of the year, but such variation was higher in the grazed site. Using different methods of estimation of BNPP, we estimated maximum values of 1241 and 723 g m-2 year -1 for the grazed and ungrazed sites, respectively. We estimated that very fine root productivity was almost twice as high at the grazed site as at the ungrazed one, despite the fact that both sites had similar total live biomass, and root turnover rate was twofold at the grazed site.